Drug Treatment of Hypertension: Controlling elevated blood pressure - Ryan, Douglas R. (1991)
Hypertension is an important contributor to cardiovascular disease, which accounts for about half of all deaths in Western societies. Proper control of elevated blood pressure is therefore important. Support has grown for an approach to care in which antihypertensive drug therapy is individually tailored for each patient. Management strategy based on this approach is discussed, and the advantages and disadvantages of the various antihypertensive agents are reviewed.